2010
DOI: 10.1590/s0102-77862010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Climatologia de frentes frias sobre a Região Metropolitana de São Paulo (RMSP), e sua influência na limnologia dos reservatórios de abastecimento de água

Abstract: Este trabalho apresenta uma análise da climatologia de frentes frias e do regime de ventos induzido por esses fenômenos sobre a Região Metropolitana de São Paulo (RMSP), no período de 21 anos (1987 a 2007). Foram utilizados dados de vento da estação meteorológica do IAG/USP, localizada no bairro da Água Funda - São Paulo - SP. Os resultados mostram que três frentes, em média, chegam a RMSP mensalmente, sendo que sua freqüência é maior nos meses de março a maio, e de agosto a dezembro. Com relação ao vento, ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 10 publications
0
21
0
6
Order By: Relevance
“…Morais et al (2010), for example, showed mixing processes of subtropical reservoirs few days prior to a cold front passage. Reservoirs with longer water retention times provide ideal conditions for phytoplankton blooms, by retaining algal biomass for longer periods (Soares et al, 2008).…”
mentioning
confidence: 99%
“…Morais et al (2010), for example, showed mixing processes of subtropical reservoirs few days prior to a cold front passage. Reservoirs with longer water retention times provide ideal conditions for phytoplankton blooms, by retaining algal biomass for longer periods (Soares et al, 2008).…”
mentioning
confidence: 99%
“…Os autores obtiveram uma média anual de 43 frentes frias e pouca variabilidade intersazonal (12 sistemas na primavera e variação de 9 a 10,5 sistemas nas demais estações do ano). Na cidade de São Paulo, Dametto e Rocha (2005) e Morais et al (2010) também obtiveram a maior ocorrência de frentes frias na primavera. Segundo Dametto e Rocha (2005), nessa região a média anual é de 35 frentes e a sazonal de 10,7 sistemas na primavera, 10,2 no inverno, 8,4 no verão e 8,0 no outono.…”
unclassified
“…To the south are the reservoirs of Billings and Guarapiranga, which are responsible for supplying water to the city. According to Moraes et al (2010), the maximum depths in each reservoir are 25 and 13 m, for Billings and Guarapiranga respectively, and are thus considered to be shallow reservoirs.…”
Section: Methodsmentioning
confidence: 99%
“…The vertical structure of tropical reservoirs is susceptible to stratification and the mixing process originating from weather events, as documented in Tundisi et al (2004Tundisi et al ( , 2010 and Moraes et al (2010). These studies showed that, according to the variability of wind stress and regimes, aquatic ecosystems present several responses in their physical, chemical, and biological variables.…”
Section: Introductionmentioning
confidence: 92%